Studi Perbandingan Metode MABAC dan WASPAS dengan Pembobotan ROC dalam Sistem Pendukung Keputusan Pemilihan Supplier Terbaik - Pratiwi, Heny; Sa’ad, Muhammad Ibnu; Hasiholan, Jundro Daud (Forum Kerjasama Pendidikan Tinggi, 2025)
The selection of the right supplier is a crucial factor in the supply chain to ensure product quality, cost efficiency, and timely delivery. This study aims to determine the best supplier by comparing two multi-criteria decision-making methods: Multi-Attributive Border Approximation Area Comparison (MABAC) and Weighted Aggregated Sum Product Assessment (WASPAS). Five key criteria were used in the evaluation: product quality, price, delivery punctuality, service and responsiveness, and reputation and trust. The analysis results show that PT. Indo Makmur (A1) consistently ranked first in both methods, with the highest scores of 0.456 (MABAC) and 0.982 (WASPAS), making it the recommended supplier. PT. Sukses Bersama (A7) and PT. Cahaya Abadi (A3) ranked second and third in both methods, indicating good performance. Meanwhile, UD. Sentosa Jaya (A4) ranked the lowest in both methods, suggesting that this supplier is less competitive than the other alternatives. The comparison of results between MABAC and WASPAS methods demonstrates ranking consistency, confirming that both methods can be reliably used in decision-making. This study provides data-driven recommendations for companies in selecting the best supplier, thereby enhancing supply chain efficiency and supporting long-term business strategies.